Teacher Assistance in Compiling HOTS Assessment Instruments Through ChatGPT at Madrasah Ibtidaiyah - Jamilatun Nafi'ah; Dukan Jauhari Faruq; Rizqiyah Ratu Balqis (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2025)
The purpose of this service is to assist teachers at the elementary level in compiling HOTS assessment instruments using the help of AI Chat GPT. This activity was attended by all teachers at Madrasah Ibtidaiyah Mambaul Hidayah with a total of 12 teachers, where in the assistance pre-test and post-test were given by the teachers offline. This service uses a service-learning strategy by not involving students because the form of direct service is carried out to madrasah teachers on a collaborative and practical basis. Based on the results of the training it showed an increase in teachers' understanding by 68% from the initial 46%. Obstacles related to the preparation of principles are reduced and teachers' ability to prepare HOTS foundation instruments shows better ability than before. The final result of this mentoring goal is in the form of an assessment instrument that teachers can prepare to test on students at the Madrasah year-end foundation activities in even semesters. This service also produces a teacher competency development program through the Digital Pedagogy Learning Community.